Src and Memory: A Study of Filial Imprinting and Predispositions in the Domestic Chick - Meparishvili, Maia; Chitadze, Lela; Lagani, Vincenzo; McCabe, Brian; Solomonia, Revaz (Frontiers in Physiology, 2021)
Visual imprinting is a learning process whereby young animals come to prefer a visual stimulus after exposure to it (training). The available evidence indicates that the intermediate medial mesopallium (IMM) in the domestic chick forebrain is a site of memory formation during visual imprinting. We have studied the role of Src kinase, an important non-receptor tyrosine kinase, in memory formation. Amounts of total Src (Total-Src) and its two phosphorylated forms, at tyrosine-416 (activated, 416P-Src) and at tyrosine-527 (inhibited, 527P-Src) were measured 1 h and 24 h after training, in the IMM and in a control brain region, the posterior pole of nidopallium (PPN). One hour after training, in the left IMM, we observed a positive correlation attributable to learning between amount of 527P-Src and learning strength; there was also a positive correlation between 416P-Src and learning strength that was attributable to a predisposition to learn readily. Twenty-four hours after training, amount of Total-Src increased with learning strength in both the left and right IMM and amount of 527P-Src increased with learning strength only in the left IMM; both correlations were attributable to learning. A further, negative, correlation between learning strength and 416P/TotalSrc in the left IMM reflected a predisposition to learn. No learning-related changes were found in the PPN control region. We suggest that there are two pools of Src; one of them in an active state and reflecting a predisposition to learn, and a second one in an inhibited condition, which increases as a result of learning. These two pools may represent two or more signaling pathways: one pathway downstream of Src activated by tyrosine-416 phosphorylation and another upstream of Src, keeping the enzyme in an inactivated state via phosphorylation of tyrosine-527.